Alkoxy Tetrazine Substitution at a Boron Center: A Strategy for Synthesizing Highly Fluorogenic Hydrophilic Probes. (30th January 2018) - Wu, Min; Wu, Xiaoai; Wang, Yayue; Gu, Lei; You, Jiao; Wu, Haoxing; Feng, Ping
Abstract: Strongly fluorogenic boron dipyrromethene (BODIPY)–tetrazine probes have been obtained by introducing an alkoxy tetrazine fragment at the boron center. The fluorescence signal from these probes strongly increases by up to 225‐fold after reaction with bioorthogonal coupling partners, and the hydrophilicity of probes is improved, such that they are suitable for live‐cell imaging. Abstract : Turn up the glow ! A series of boron dipyrromethene (BODIPY)–tetrazine fluorogenic probes are obtained by introducing alkoxy tetrazine fragments into the boron center. The resulting hydrophilic probes exhibit up to 100‐fold fluorescence increase upon reaction with bioorthogonal coupling partners, and are suitable for live‐cell imaging.